Drought and heat tolerance in coffee: a review - Gichimu, Bernard M.; Cheserek, J.J. (My University, 2012)
Climatic variability is the main factor responsible for the fluctuations in the coffee yield in the world. The relationships between the climatic parameters and the agricultural production are quite complex, because environmental factors affect the growth and the development of plants under different forms during the phenological phases of the coffee crop. Such environmental factors include reduced rainfall and high temperatures both of which majorly contribute to drought. This paper briefly reviews some of the important aspects of drought and heat tolerance in coffee. It highlights the impacts of draught and high temperatures in coffee production, tolerance mechanisms, necessary interventions, selection challenges and current advances towards development of drought and heat tolerant coffee cultivars.
Keywords: coffee; Water Stress; High Temperatures; Tolerance Mechanisms